2019
DOI: 10.1007/s11356-019-05027-y
|View full text |Cite
|
Sign up to set email alerts
|

Depollution of mining effluents: innovative mobilization of plant resources

Abstract: Based on the ability of some specific aquatic plants to concentrate metals in their roots, we propose an innovative biosorption system to clean up mining effluents. The system we propose represents an interesting solution to an important environmental problem, the decontamination of metal-polluted water and prevention of dispersal of metals into the environment. The solution presented is a form of ecological recycling of Zn, an essential primary metal in many industrial applications. Finally, the methodology d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…As for the comparison with previously published biosorption data, most of the biomaterials reported in literature for metal removal with column systems are based on agricultural wastes recycled from the food production chain (e.g., Pérez Marín et al 2009 ; Iqbal et al 2013 ; Chao et al 2014 ; Abdolali et al 2017 ; Dong and Lin 2017 ). A fewer number of studies took into consideration plant biomass (Karunasagar et al 2005 ; Stanovych et al 2019 ), and, to the best of our knowledge, only one paper tested P. australis dried biomass in column mode for the removal of Cr(VI) (Lagiopoulos et al 2017 ). The comparison of the results obtained here with those previously reported in the literature is complicated by the fact that the metal removal efficiencies, in addition to the type of biosorbent (often chemically modified prior its use as biosorbent), are strongly affected by a number of operating parameters such as the percolation rate and the metal concentration of the influent solution (Abdolali et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for the comparison with previously published biosorption data, most of the biomaterials reported in literature for metal removal with column systems are based on agricultural wastes recycled from the food production chain (e.g., Pérez Marín et al 2009 ; Iqbal et al 2013 ; Chao et al 2014 ; Abdolali et al 2017 ; Dong and Lin 2017 ). A fewer number of studies took into consideration plant biomass (Karunasagar et al 2005 ; Stanovych et al 2019 ), and, to the best of our knowledge, only one paper tested P. australis dried biomass in column mode for the removal of Cr(VI) (Lagiopoulos et al 2017 ). The comparison of the results obtained here with those previously reported in the literature is complicated by the fact that the metal removal efficiencies, in addition to the type of biosorbent (often chemically modified prior its use as biosorbent), are strongly affected by a number of operating parameters such as the percolation rate and the metal concentration of the influent solution (Abdolali et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that E. crassipes roots are rich in hemicellulose (Ruan et al, 2016) and thus in carboxylate functions. Recently, we have proven by mathematical fitting of FTIR-ATR assessments that roots of many aquatic plants (M. aquatica, E. crassipes, P. stratiotes, and L. peploides) are rich in carboxylate functions (Stanovych et al, 2019). The natural affinity of carboxylate moieties for transition metallic elements is consistent with functional features of aquatic plants and the biosorption performances of their roots.…”
Section: Potential Mechanismsmentioning
confidence: 86%
“…So it was fair to assume that precipitation of the metallic species would prevent efficient adsorption on the biomaterials. ii) Nonetheless, we have recently shown that materials based on roots of aquatic plants are rich in carboxylate functions (Stanovych et al, 2019;De Laet et al, 2019). This fact could make roots of our group 4 plants more suitable than the biosorbents of other groups for the biosorption of Pd, owing to their stronger affinity for transition metals based on the formation of metal carboxylate salts.…”
Section: Effect Of Phmentioning
confidence: 95%
See 2 more Smart Citations